Assessment of knowledge level and Sources of information among Hypertensive Patients in Tishreen Hospital - Nizamli, Frial; Hasan, Nisreen (Latakia University Journal -Medical Sciences Series, 2018)
introduction: Hypertension is a great health problem in the all the world, and causes many of complications such as heart and renal diseases. Aim: To assess the level of knowledge on hypertension among hypertensive and sources of information. Method: A descriptive study was conducted among 50 patients who entered Tishreen university. Questionnaire on different domains of hypertension such as general knowledge, complications, treatment and life style, as well as sources of information was used to collect relevant information. Each statement was given a score of one if it was answered correctly and zero for a wrong answer. Out of a total score, a score of seventy percent and above was considered good knowledge , between thirty percent and seventy considered moderate, less than thirty considered poor knowledge . Results: Most of participants, were between 50-59 years (44%), (54%) were males and (46%) were females. doctors was found to be the most utilized source of information on high blood pressure. The level of awareness of high blood pressure was 75.5%. Recommendation: Future study about educational needs for these patients and comparative study about knowledge level and information sources between rural and urban hypertensive's are recommended. تقييم مستوى المعرفة و مصادر المعلومات عند مرضى ارتفاع الضغط الشرياني في مستشفى تشرين الجامعي - المقدمة: يعتبر ارتفاع ضغط الدم الشرياني مشكلة صحية كبيرة في جميع أنحاء العالم ، فهو يسبب العديد من المضاعفات الخطيرة كالأمراض القلبية والكلوية. - الهدف: يهدف هذا البحث إلى تقييم مستوى المعرفة لدى مرضى ارتفاع ضغط الدم والتعرف على مصادر المعلومات المستخدمة من قبلهم. - مواد وطرق البحث: أجريت هذه الدراسة الوصفية في مستشفى تشرين الجامعي باللاذقية على عينة مؤلفة من50 مريضا مراجعا في الفترة الواقعة بين أيار 2016 و تموز 2016.، تراوحت أعمارهم بين 30 و 65 سنة. تم جمع البيانات من خلال استبيان يحتوي مصادر المعلومات ومدى معرفة المرضى حول تعريف الضغط، الحمية، نمط الحياة، العلاج الدوائي، المضاعفات. تم اعتبار 70% وما فوق مستوى جيد للمعرفة و30- 70 % مستوى متوسط، 30% ومادون مستوى ضعيف. - النتائج: بينت الدراسة أن النسبة الأكبر من العينة 44% كانت بين عمر50-59 وأن نسبة 46% الإناث و 54% ذكور، وأن الأطباء هم من أكثر المصادر استخداما للحصول على المعلومات كما أظهرت الدراسة أن مستوى المعرفة لدى العينة كان جيدا 75،5%. - التوصيات: توصي هذه الدراسة بإجراء دراسات مستقبلية لتقييم الاحتياجات التعليمية لهؤلاء المرضى وإجراء دراسة مقارنة بين مستوى المعرفة ومصادر المعلومات بين قاطني الريف والمدينة.